Recovering the Sabbath:: Sunday Observance as a Universal Human Right and Civic Cooperationism - McLaughlin, SJ, Brett (Lumen et Vita, 2020)
This paper advances that the religion-state model of cooperationism would allow for civil legislation to protect the Sabbath. Unfortunately, the models of separation or accommodationism have predominated in the U.S. since the Bill of Rights. However, the cooperationist regime, such as in Germany, recognizes the universal common good present in religious legislation. The cooperationist model is present in most European countries; it readily preserves democracy. The Judeo-Christian tradition may be the source of advocacy for Sunday closing laws, yet a weekly rest from the economy serves all citizens.